Influence of the Growth Substrate on the Internal Quantum Efficiency of AlGaN/AlN Multiple Quantum Wells Governed by Carrier Localization. Issue 4 (21st December 2020) - Jacopin, Gwénolé; Frankerl, Christian; Tillner, Nadine; Davies, Matthew John; Rossbach, Georg; Brandl, Christian; Hoffmann, Marc Patrick; Zeisel, Roland; Hoffmann, Axel; Lugauer, Hans-Jürgen
Abstract : The influence of the growth substrate on the internal quantum efficiency (IQE) of deep ultraviolet light‐emitting diodes is studied. Two nominally identical Al‐rich AlGaN/AlN multi‐quantum‐well (MQW) structures grown by metal–organic vapor phase epitaxy (MOVPE) on different substrates are investigated. The first MQW structure is grown on a native AlN substrate, whereas the second one is deposited on an AlN template on sapphire. By the combination of atomic force microscopy (AFM), photoluminescence (PL), and cathodoluminescence (CL) spectroscopy, it is demonstrated that the dislocation‐mediated spiral growth of MQWs on sapphire results in the more efficient localization of carriers. This effect helps to prevent nonradiative carrier recombination at point defects, improving the IQE of the structure. Abstract : The growth substrate influences the efficiency of deep ultraviolet light‐emitting diodes. By combining atomic force microscopy, photoluminescence, and cathodoluminescence spectroscopy, the authors compare two AlGaN/AlN multi‐quantum‐well structures grown by metal–organic vapor phase epitaxy on different substrates: a native AlN substrate and an AlN template on sapphire. It is demonstrated that the spiral growth on sapphire results in more efficient carrier localization.